Pyridostigmine improves hand grip strength in patients with myalgic encephalomyelitis/chronic fatigue syndrome - Schlömer, Ella; Stein, Elisa; Kedor, Claudia; Rust, Rebekka; Brock, Anna; Wittke, Kirsten; Scheibenbogen, Carmen; Kim, Laura (Frontiers in Neuroscience, 2025)
BackgroundMyalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a multisystemic disease characterized by exertional intolerance and fatigue which is often accompanied by muscle weakness and fatiguability. A study showed efficacy of the acetylcholinesterase inhibitor pyridostigmine on cardiac output in ME/CFS patients. Pyridostigmine is currently used off-label in ME/CFS and postural orthostatic tachycardia syndrome.MethodsWe evaluated the effect of pyridostigmine on hand grip strength in 20 patients with post-infectious ME/CFS. Hand grip strength testing was performed ten times using an electric dynamometer and was repeated after 1 h. In a second test, 30 mg of pyridostigmine was given immediately after the first measurement. Orthostatic function was assessed using a passive standing test. Neurological examination and autoantibody testing were performed to rule out a diagnosis of myasthenia gravis.ResultsAll patients had reduced maximum hand grip strength with a median of 16.45 kg (IQR: 11.45 kg–22.8 kg). Hand grip strength was diminished by a median of 4.65 kg after 1 h. In contrast, 1 h after pyridostigmine administration, patients showed an improvement in maximum hand grip strength with a median increase of 2.6 kg. The maximum hand grip strength after exertion was about 1.5-fold higher with then without pyridostigmine (p = 0.01). The increase in heart rate from lying to standing was median 17 beats per minute without pyridostigmine (IQR: 13 beats per minute – 23 beats per minute) and 13 beats per minute (IQR: 9 beats per minute – 20 beats per minute) (p = 0.017) with pyridostigmine. None of the patients tested positive for myasthenia gravis specific autoantibodies.ConclusionPyridostigmine exerts an immediate effect on muscle strength and orthostatic function. This may be attributed to increased acetylcholine availability at neuromuscular junctions, and its augmentation of parasympathetic tone.